Performance analysis for the UK's first 5th generation heat network – The BEN case study at LSBU. (15th March 2022) - Gillich, Aaron; Godefroy, Julie; Ford, Andy; Hewitt, Mark; L'Hostis, Jonathan
Abstract: The decarbonisation of heat requires a transition from gas boilers to low-carbon heating systems such as heat pumps. Efficiency gains can be achieved by linking heating systems through ambient loops called Fifth Generation District Heating and Cooling (5GDHC) networks. The UK needs working demonstrators to understand both the technical and practical challenges in the heat transition. The Balanced Energy Network (BEN) links two buildings on LSBU's campus and is the UK's first 5GDHC system at scale and among the first in the world to be retrofit in parallel to an incumbent gas system and include an active demand side response control system to toggle between energy vectors in way that minimises cost and carbon emissions. This paper presents performance data from its first year of operation in baseline mode, as it was commissioned and optimised. High temperature heat pumps were retrofit to an existing gas boiler circuit and match the 79 °C output temperature of the gas boiler system. No fabric upgrades were required and no pipes, ducts or heat emitters were resized, however the system maintained performance to reduce overall building carbon emissions by 13% and gas use by 40% across both buildings compared to the pervious heating season while the system was in use. Highlights: First known UK 5th Gen ambient heat network retrofit to existing buildings. Demonstration of high temperature heat pumps (79 °C) maintaining a high COP. Performance data from heat pumps retrofit into existing gas heating systems. Demonstration of a phased transition from gas to heat pumps in complex buildings. Up to 40% reduction in use CO2 emissions with opportunities to optimise over time.